Mobilizing agroecology to reconcile food and biodiversity trade-offs - Jones, Sarah; Chemarin, Charlotte; Orduña, Fernando; Mosnier, Aline (2025)
The interconnected challenges of food insecurity, climate change, biodiversity loss, and water scarcity require integrated solutions. Agroecology is gaining traction as a potential approach for harmonizing these major global issues. To test the effect of widespread use of agroecological practices, we developed and applied an agroecology module for an integrated food system assessment model, the FABLE Calculator. Effects of diversified cropping practices on yield, biodiversity, soil organic carbon (SOC) and labour inputs were estimated from existing systematic reviews. Current practice distribution was estimated from freely available global datasets and adjusted using local agricultural expert knowledge. Building on pathways designed by 22 FABLE countries teams and for six rest of the world regions, we explored the effect of increasing the use of diversified farming practices to cover 100% of global cropland by 2050. Results show that scaling agroecological practices on cropland in combination with shifting to healthy diets has a substantial positive impact on- and off-farm biodiversity and net greenhouse gas emissions, without compromising global food security.